When Nostalgia Tilts to Sad: Anticipatory and Personal Nostalgia - Batcho, Krystine I. (Frontiers in Psychology, 2020)
Abstract Contemporary research has showcased many benefits of nostalgia, but its bittersweet character and historical reputation as unhealthy raise the possibility of less favorable impacts. In recent studies, daily diary data highlighted nostalgia’s mixed valence and suggested that nostalgia is more strongly associated with negative feelings. Variables that influence the adaptive or maladaptive dimensions of nostalgia have not yet been fully explored. Recently, a focus on when nostalgia is experienced relative to past and future was introduced in the construct of anticipatory nostalgia, missing the present prematurely before it has become past. Distinct from personal nostalgia, anticipatory nostalgia was found to be characterized by difficulty enjoying the present and a tendency toward sadness and worry. The present study examines the distinctive dynamics at play in anticipatory and personal nostalgia by exploring the relationship between each type of dispositional nostalgia and reported experience with happy and sad stories. The Nostalgia Inventory, the Survey of Anticipatory Nostalgia, and a brief form of the PANAS were completed by 144 undergraduates (110 women), who rated their exposure and reactions to happy and sad stories. Reported frequency of exposure to happy and sad stories was related to dispositional happiness and sadness. Personal and anticipatory nostalgia did not differ in frequency of exposure to happy and sad stories, but they did differ in reactivity to and learning from sad stories. Findings highlight the importance of the timing of nostalgia, consistent with the distinction between nostalgia for the past and nostalgia for what is still present.